Revolusi Intelektual Ekonomi Islam 1960–1980: Arah Baru Kelahiran Paradigma Ekonomi Syariah Modern - Saeed Fayzul Hayat; Idris Parakkasi; Fatimah Fatimah (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
This study aims to provide a comprehensive analysis of the emergence of the modern Islamic economic paradigm during the critical period of 1960–1980. Specifically, the research examines how global ideological crises, the resurgence of Islamic intellectual thought, and the institutionalization of Islamic financial entities jointly contributed to shaping the foundations of contemporary Islamic economics. Employing a qualitative approach with a historical-critical design, the study utilizes an in-depth literature-based data collection method, drawing from seminal works of major Islamic economic thinkers such as Mawdudi, al-Sadr, Siddiqi, Khurshid Ahmad, and Chapra, alongside key historical documents including the archives of Mit Ghamr, Dubai Islamic Bank, and the Islamic Development Bank. Data were analyzed using content analysis, discourse analysis, and historical interpretation to identify conceptual patterns, socio-political contexts, and institutional developments that characterized the era. The findings reveal that the period of 1960–1980 marked a pivotal epistemological transformation from normative Islamic economic discourse to a more structured scientific discipline. It also witnessed the emergence of modern Islamic financial instruments and the consolidation of the Islamic economic paradigm through international institutional development. These results demonstrate that the birth of modern Islamic economics is the outcome of a dynamic interplay between ideas, institutions, and global transformations.